PENGEMBANGAN POTENSI UMKM MELALUI PEMANFAATAN SUMBER DAYA LOKAL (STUDI KASUS DESA TAWANGHARJO, KECAMATAN GIRIWOYO, KABUPATEN WONOGIRI) - Agung Wibowo; Riyan Juniarto Putro; Indah Aprilliyani; Imam Mahmuddi Muharram (Inisiasi, 2024)
This study aims to explore and develop the potential of MSMEs in Tawangharjo Village, Giriwoyo District, Wonogiri Regency, which is rich in natural resources such as agriculture, livestock, handicrafts, and processed foods. A qualitative research approach with a case study method was employed, involving in-depth interviews, participatory observations, Focus Group Discussions (FGDs), and documentation with various local stakeholders.The findings indicate that MSMEs in Tawangharjo Village have effectively utilized local resources through various strategies, including optimizing the use of local raw materials, developing value-added products, enhancing skills and knowledge through training and mentoring, strengthening marketing networks, and diversifying products and innovations. Collaboration with external parties such as the InaMikro company has also positively contributed to improving the legality and market access of local MSMEs.However, these MSMEs still face several challenges, including limited access to modern technology, capital, and broader markets. Continuous intervention from the government and related institutions is necessary to overcome these obstacles. Overall, this community service program has successfully increased productivity, income, employment absorption, and community empowerment in Tawangharjo Village. The implementation of this local resource-based MSME development strategy is expected to serve as a model for other regions in promoting sustainable and independent rural economic growth.